Cadmium contamination of soils and crops by long term use of raw effluent, ground and canal waters in agricultural lands - Hussain, A.; Murtaza, G.; Ghafoor, A.; Basra, S.M.A.; Qadir, Manzoor; Sabir, M. (2010)
Water scarcity in agriculture sector forced farmers to use city wastewater without any regard of its quality effects on environment and resultant contamination of soils and plants, particularly with heavy metals. A survey of effluent, tube well and canal water irrigated areas in Faisalabad, Pakistan was conducted to appraise Cd concentration in these waters and soils, and its uptake by cereal and legume crops. Water, soil and plant (seeds, shoot & roots) samples were collected and analyzed for Cd concentration. Results illustrated that wastewater contained 11.0 and 3.7 times higher Cd than tube well and canal waters, respectively. Location-wise the lowest Cd concentration was 0.6 ?g L-1 at Bypass Samandari Road (BSR) while the highest was 1.4 ?g L-1 at Malkhanwala (MW). Maximum AB-DTPA extractable Cd (0.30 mg kg-1 & 0.248 mg kg-1) was found in soil samples collected from 0-15 cm depths at Uchkera and Ghulam Muhammad Abad (GMA), respectively. It was the lowest (0.04 mg kg-1) in soil samples collected from Chak No. 235/RB (C235) location. Long term effluent irrigation resulted in 248 and 260% increase in Cd contents at 0-15 cm depth of soils compared to tube well and canal waters irrigated soils, respectively. In all the cases, Cd was within safe limits. About 70% of the metal was deposited in upper 30 cm layers. Seeds of effluent irrigated chickpea acquired the highest concentration of Cd (0.177 mg kg-1), while was the lowest in wheat seeds (0.034 mg kg-1). Concentration of Cd was higher in mungbean shoots (0.62 mg kg-1) than in wheat shoots. The order for Cd concentration in seeds was chickpea > maize > mungbean > wheat for wastewater irrigated crops. Similar trend of Cd concentration was observed in tube well and canal waters irrigated crops.